Beyond the Ethnic Enclave Economy. (31st July 2014) - Light, Ivan; Sabagh, Georges; Bozorgmehr, Mehdi; Der-Martirosian, Claudia
Abstract : The terms "ethnic economy" and "ethnic enclave economy" designate an immigrant or minority business and employment sector that coexists with the general economy. Users often treat these terms as synonymous. In fact, they are not. The concept of ethnic enclave economy derives from the labor segmentation literature, whereas the concept of ethnic economy derives from the middleman minorities literature. The derivations have shaped the problems that both concepts address. The strenuous debate about relative wages in the ethnic enclave versus the general economy is a case in point. When conceptualized in terms of an ethnic economy, the salience of this debate greatly diminishes. Agreeing that the concept of ethnic enclave economy is useful, we nonetheless claim that it is less general than the older concept of the ethnic economy. Indeed, we show that the ethnic enclave economy is really a special case of the ethnic economy. Evidence for this conclusion derives, in part, from our survey of Iranian immigrants in Los Angeles, the results of which fit the older ethnic economy concept but cannot be squeezed into the concept of an ethnic enclave economy.